Gene-targeted deletion and replacement mutations of the T-cell receptor beta-chain enhancer: the role of enhancer elements in controlling V(D)J recombination accessibility. - Bories, J C (1996)
To assess the role of transcriptional enhancers in regulating accessibility of the T-cell receptor beta-chain (TCRbeta) locus, we generated embryonic stem cell lines in which a single allelic copy of the endogenous TCRbeta enhancer (Ebeta) was either deleted or replaced with the immunoglobulin heavy-chain intronic enhancer. We assayed the effects of these mutations on activation of the TCRbeta locus in normal T- and B-lineage cells by RAG-2 (recombination-activating gene 2)-deficient blastocyst complementation. We found that Ebeta is required for rearrangement and germ-line transcription of the TCRbeta locus in T-lineage cells. In the absence of Ebeta, the heavy-chain intronic enhancer partially supported joining region beta-chain rearrangement in T- but not in B-lineage cells. However, ability of the heavy-chain intronic enhancer to induce rearrangements was blocked by linkage to an expressed neomycin-resistance gene (neo(r)). These results demonstrate a critical role for Ebeta in promoting accessibility of the TCRbeta locus and suggest that additional negative elements may cooperate to further modulate this process.